KEPUNAHAN NAMA-NAMA TRADISIONAL BUDAYA MASYARAKAT BUTON - Bat Mang (Institut Agama Islam Negeri (IAIN) Metro, 2017)
This study aims to reveal the level of extinction traditional names Buton community culture in the last twenty years. This study is a qualitative research study use documentation, the data in this study derived from the documents in the archive form birth certificate and original family card Buton sourced from the Civil Registry Office Buton 2015. Documentation method used in this study because the authors analyze the document. The data in this study are the names of the traditional culture of Buton on file birth certificates and family registration card at the Civil Registry Office Buton. The results of this study indicate the destruction of cultural traditional names Buton is a process that happens gradually eventually disappear altogether in the last year. It can be seen from the generation born before the very few who use the name of the area distinctively; until finally began in 2015 has been completely disappears. Buton people now losing regional identity that is not easily known only by name as easily recognize the Moluccas or Batak people who remain loyal to use surnames to their name. The cultural heritage that should be proud of and preserve it faded because of the influence of the association, modernization, and feelings of inferiority society. The names of the ancestral cultural heritage was confirmed in ten or twenty years when the older generation who still use a traditional name that ends their life then death gong traditional names Buton at that moment must sign of the death of a culture.